(untitled) (Research, Society and Development, 2021)
Multicampi Saúde is an extension project of the Federal University of Pará (UFPA) that seeks to strengthen the professional training of undergraduate students in health courses and the like to integrate them into health services, particularly in the area of Attention Basic, focusing on child health care policy. Objective: to report how experiences lived by nursing students during extension activities carried out in a municipality in the State of Pará. Methodology: a descriptive study, of the experience report type, developed by two nursing students from a Multicampi Saúde, developed in Castanhal, in the state of Pará, in the month of November 2019. Results: the activities were developed based on a work plan prepared by the tutors based on the monitoring of a “guide child” and his family, in addition to the other users of the Unified Health System (SUS). The activities carried out were: nursing consultation, home visit and educational actions for the community and the health team. Participation in a multiprofessional team enabled interaction between professionals and broader assistance and care from users. Final Considerations: an integration between teaching and service offers the best training for teachers, students and health service professionals, being an important strategy to achieve changes in the training process of academics and future health professionals.